Picasso | encounters - Clarke, Jay A. 1966-; McCully, Marilyn (Yale University Press, 2017)
Although Pablo Picasso (1881-1973) is often thought of as a solitary genius, his career was fueled by the inspiration he drew from both personal and collegial relationships. Picasso practiced printmaking throughout his career-an interest that inherently fostered collaboration, as it brought him in contact with numerous printers and publishers. At the same time, his many famous muses-Marie-Therese Walter, Dora Maar, and others-influenced both his techniques and his imagery. This book features thirty-five of Picasso's most important prints that showcase the artistic exchange vital to his process. It includes his first major etching from 1904, portraits of his lovers and family members, and prints that transform motifs by Rembrandt, Manet, and other earlier artists, such as an interpretation of Rembrandt's Ecce Homo from 1970. 'Picasso | Encounters' considers the artist's major statements in printmaking throughout his career
Published on the occasion of the exhibition 'Picasso | Encounters', Clark Institute Williamstwon, Massachusetts, June 4 - August 27, 2017
Keywords: Picasso, Pablo -- 1881-1973; Druckgrafik; Bildband; Ausstellungskatalog -- Sterling and Francine Clark Art Institute -- 04.06.2017-27.08.2017 -- Williamstown, Mass.